Enriched environment ameliorates propagation of tau pathology and improves cognition in rat model of tauopathy - Mate, Veronika; Smolek, Tomas; Kazmerova, Zuzana Vince; Jadhav, Santosh; Brezovakova, Veronika; Jurkanin, Bernadeta; Uhrinova, Ivana; Basheer, Neha; Zilka, Norbert; Katina, Stanislav; Novak, Petr (Frontiers in Aging Neuroscience, 2022)
Introduction: The typical symptoms of Alzheimer’s disease (AD) are cognitive impairment, disrupted spatial orientation, behavioural and psychiatric abnormalities, and later motor deficits. Neuropathologically, AD is characterised by deposits of pathological forms of endogenous proteins – amyloid β, and neurofibrillary tau protein pathology. The latter closely correlates with brain atrophy and clinical impairment. Pharmacological therapies for these pathologies are largely absent, raising the question whether non-pharmacological interventions could be efficacious. Environmental factors can play a role in the manifestation of AD. It is unknown whether enriched environment (EE) can ameliorate the propagation of protein aggregates or their toxic components. Methods: We injected insoluble tau extracts from human brains with AD (600 ng or 900 ng per animal) into hippocampi of SHR72 transgenic rats that express non mutated truncated human tau 151-391/4R, but usually do not develop hippocampal tangles. The rats had either standard housing, or could access an EE 5x/week for 3 months. Behavioural analysis included the Morris Water Maze (MWM). Histological analysis was used to assess the propagation of tau pathology. Results: Animals exposed to EE performed better in the MWM (spatial acquisition duration and total distance, probe test); unexposed animals improved over the course of acquisition trials, but their mean performance remained below that of the EE group. Enriched environment abrogated tau propagation and hippocampal tangle formation in the 600 ng group; in the 900 ng group, tangle formation was ~10-fold of the 600 ng group, and unaffected by EE. Conclusions: Even a small difference in the amount of injected human AD tau can cause a pronounced difference in the number of resulting tangles. EE leads to a noticeably better spatial navigation performance of tau-injected animals. Furthermore, EE seems to be able to slow down tau pathology progression, indicating the possible utility of similar interventions in early stages of AD where tangle loads are still low. Acknowledgments: The work is supported by research grants APVV-18-0515, APVV-17-0642, VEGA 2/0127/22 and VEGA 2/0110/20.